Can precious metals hedge geopolitical risk? Fresh sight using wavelet coherence analysis. (December 2022) - Cheng, Sheng; Zhang, Zongyou; Cao, Yan
Abstract: Based on wavelet coherence analysis, this paper explores whether precious metals can be used to hedge geopolitical risk (GPR) and whether there is an asymmetry in the hedging effect when GPR rises or falls in time and frequency domains. In addition, we obtain the lead-lag relationship between precious metals and GPR under different time-frequency effects. The main findings are summarized as follows. First, gold and silver are good assets to hedge against GPR in the short and medium term. Second, the relationship between GPR and precious metals shows a significant asymmetry when GPR rises and falls. Third, all four precious metals can hedge both GPR and the negative change of GPR in the medium term. Finally, it is worth noting that both gold and silver are leaders in GPR changes. These new findings in this paper provide an essential reference for investors and policymakers from different time scale perspectives. Highlights: The correlation and lead-lag relationship between geopolitical risk and precious metals are analyzed employing wavelet coherence. Gold and silver are good assets to hedge against GPR in the short and medium term. The relationship between GPR and precious metals shows a significant asymmetry when GPR rises and falls. Both gold and silver are leaders in GPR changes.